Media's Effects on People's Perceptions and Intentions in Post-Disaster Recovery – a Case Study of the Great East Japan Earthquake - John W. Cheng; Hitoshi Mitomo; Tokio Otsuka; Stefan Y. Jeon (International Telecommunications Society (ITS), 2015)
Prior studies show that both mass and social media have played an influential role after the Great East Japan Earthquake, in particular, media information can affect a person's perception of the disaster as well as their behavioural intention of post-disaster activities. However, currently the underlying mechanism is still not clear, for instance, what kinds of perception did mass and social media cultivate? Were they complementing or contracting with each other? And how different kinds of perceptions affect people's intention of post-disaster activities? This study attempts to understand the mechanism between the use of media and their effects on a person's perception of the disaster and the behaviour intention of post-disaster activities. Using data collected from the three prefectures that were hit by the disaster directly and structural equation modelling, three key findings are identified. First, the use of mass media has a dominating effect of a person's perception of the disaster, but to a certain extent, its effects can be regulated by social media. Second, among different perceptions of the disaster, the perception of bonds in society appears to be the most influential on people's intention of altruistic actions, civic communications, and preparation for future disasters. Third, media has a stronger influence on those who were not affected the disaster directly than those who were. These findings have some important implications for government authorities and NGOs who are working in post-disaster recovery and disaster preparation.
Keywords: 330